MHD stagnation-point flow of hybrid nanofluid with convective heated shrinking disk, viscous dissipation and Joule heating effects - Khashi’ie, Najiyah Safwa; Wahid, Nur Syahirah; Md Arifin, Norihan; Pop, Ioan (Springer, 2022)
This paper describes the MHD stagnation-point flow of Cu-Al2O3/H2O hybrid nanofluid toward a convectively heated shrinking disk with convective boundary condition, suction, Joule heating and viscous dissipation effects. Similarity transformation reduces the PDEs into a system of ODEs, which then numerically solved using the bvp4c solver. The comparison between present and previous results in certain cases shows an excellent agreement with approximately 0% relative error. Two solutions exist in which the second solution appears near to the separation value of the velocity ratio parameter. The stability analysis shows that the first solution is physically stable (realizable in practice). An increase of suction and magnetic parameters extends the critical value and aids the performance of heat transfer operation. Further, the heat transfer rate boosts while the critical values unchanged with the rise of Eckert number (implies the operating Joule heating and viscous dissipation) and Biot number (implies the operating convective boundary condition). The temperature profile reduces with the increment of velocity ratio parameter, Eckert and Biot numbers while the velocity increases with the addition of velocity ratio and magnetic parameters. This study is important in the estimation of the flow and thermal behavior for Cu-Al2O3/H2O when the physical parameters are embedded.